2009
DOI: 10.1089/hum.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Based Cancer Gene Therapy

Abstract: In view of their potent antigen-presenting capacity and ability to induce effective immune responses, dendritic cells (DCs) have become an attractive target for therapeutic manipulation of the immune system. The application of tumor-associated antigen (TAA)-expressing DCs for cancer therapy has been the subject of intensive translational investigation. Previous clinical trials demonstrated tumor-specific immune responses without any significant toxicity. However, the clinical success has been modest, because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 118 publications
2
57
0
Order By: Relevance
“…DC-based therapy originates from the unique capacity of DCs to present captured antigens to T cells, which is essential for generating specific T cell immunity [51][52][53][54]. Loading of DCs with tumor-associated antigens (TAAs) has therefore become an attractive therapeutic tool in order to generate tumorspecific T cells.…”
Section: Dc-and Nk Cell-based Immunotherapy Of Cancermentioning
confidence: 99%
“…DC-based therapy originates from the unique capacity of DCs to present captured antigens to T cells, which is essential for generating specific T cell immunity [51][52][53][54]. Loading of DCs with tumor-associated antigens (TAAs) has therefore become an attractive therapeutic tool in order to generate tumorspecific T cells.…”
Section: Dc-and Nk Cell-based Immunotherapy Of Cancermentioning
confidence: 99%
“…24,26 Several cytokines have been implicated in modulating DC function, type I IFN among them. 27,28 They have been shown to enable cross-priming of naive T cells, both by licensing DC to present exogenous antigens in an immunostimulatory way and by acting directly on T cells (Table 1). 29,30 In addition to naive T cell priming, IFN-a can also contribute to the generation of an antigen-specific cytotoxic T cell response by promoting the endogenous expression of the leukemiaassociated antigen proteinase-3/myeloblastin in myeloid leukemic cells (Figure 1).…”
Section: Indirect Effects Of Type I Ifn Through Immune Activationmentioning
confidence: 99%
“…DC have been intensively investigated as cellular adjuvants for therapeutic cancer vaccination, and since the first reported trial in lymphoma patients in 1996 (16), DC have shown an unsurpassed capacity to induce in vivo antitumor responses. However, the overall clinical response rate, if any, remains very low (17). This poor clinical outcome could be, at least in part, ascribed to the fact that most clinical DC trials to date have been performed in end-stage cancer patients, often with bulky tumor loads and a compromised immune system caused by intensive treatment schedules and/or advanced disease stage (18).…”
mentioning
confidence: 99%